Practical Multigram Approach to Conformationally Constrained α-Proline-Based Building Blocks with γ-Spiro Conjunction - Iermolenko, Ievgenii A.; Kolosov, Oleksii S.; Ostapchuk, Eugeniy N.; Lega, Dmitry A.; Derkach, Nikita O.; Levchenko, Kostiantyn V.; Makhankova, Valeriya G.; Rozhenko, Alexandr B.; Volochnyuk, Dmytro M.; Ryabukhin, Serhiy V. (Synthesis, 2024)
Unusual amino acids have arisen as an indispensable instrument at the disposal of modern medicinal chemistry. While extensively exploited as building blocks in the search for new pharmaceuticals, their application goes far beyond. They are currently involved in explorations of the structure and conformational mobility of peptides, modification and amplification of peptidomimetic activity, and others. Herein, we report an effective synthetic approach to nonplanar, conformationally restricted, sp3-enriched spirocyclic α-prolines. The protocol employs readily available nitrile-based starting materials and conventional experimental procedures. The synthetic sequence is concise and includes three principal stages (one of them a four-step telescopic process). The reactions proceed on a multigram scale affording the target prolines in overall good yields. The possibility of chiral separation of the synthesized racemic spiro prolines to both pure enantiomers is shown. The building blocks synthesized in the study are expected to have practical uses in the field of medicinal chemistry.
Keywords: amino acids; proline; spiro compounds; multigram; building blocks; medicinal chemistry; conformational rigidity